2019
DOI: 10.3344/kjp.2019.32.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Animals models of spinal cord contusion injury

Abstract: Spinal cord contusion injury is one of the most serious nervous system disorders, characterized by high morbidity and disability. To mimic spinal cord contusion in humans, various animal models of spinal contusion injury have been developed. These models have been developed in rats, mice, and monkeys. However, most of these models are developed using rats. Two types of animal models, i.e. bilateral contusion injury and unilateral contusion injury models, are developed using either a weight drop method or impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…Rodent models have become standard in the past 30 years and have been widely used in SCI research (Kwon et al, 2015). Rats are the best choice and the most widely used due to the limit field of vision of mice (Verma et al, 2019). In rat model of SCI, we observed that there was a significant improvement on motor function after EA treatment compared to Model group at 3 and 7 days time points (P < 0.01).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Rodent models have become standard in the past 30 years and have been widely used in SCI research (Kwon et al, 2015). Rats are the best choice and the most widely used due to the limit field of vision of mice (Verma et al, 2019). In rat model of SCI, we observed that there was a significant improvement on motor function after EA treatment compared to Model group at 3 and 7 days time points (P < 0.01).…”
Section: Discussionmentioning
confidence: 77%
“…For Sham group, only laminectomy was performed. The SCI model was then produced using a NYU Impactor M-III strike (a 10 g pouching rod of 2.5 mm diameter with drop of 50 mm and damage of 50 g•cm) at the T10 segment to create relatively serious injury (Verma et al, 2019). All SCI rats conformed to the following injury criteria: spinal cord ischemia and edema, formation of tail sway reflex, flicking of both body and legs, and the appearance of sluggish paralysis.…”
Section: Animals Modelmentioning
confidence: 99%
“…Notably, riluzole has an important role in protecting against excitotoxic cell death by blocking the sodium channel in the injured neurons constraining the presynaptic toggle of glutamate ( 97 ). Neuronal loss and cavity size have been reduced in SCI animal models ( 98 ). A significant improvement of sensorimotor and results of electrophysiological were demonstrated in a previous study ( 66 ).…”
Section: Pharmacological Drugs Used For the Treatment Of Sci ( mentioning
confidence: 99%
“…Rodent models are typically used in the experiments with SCI induction to assess compression-or contusion-simulating impact [9][10][11]. Though these SCI models reproduce a realistic clinical course of the spinal cord injury in humans, they have multiple drawbacks, in particular, the impossibility to induce a «standardized» defect.…”
Section: Introductionmentioning
confidence: 99%
“…In the control group of animals where only surgical approach to the spinal cord was performed (without exposure to low temperatures), the full recovery of motor activity was reported much earlier -five days after the surgery (fig 9). [11,14]. Current SCI models cause significant urinary system dysfunctions in rats, which is a serious drawback [14].…”
mentioning
confidence: 99%